If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(t + 7) = 48 Reorder the terms: 0.5(7 + t) = 48 (7 * 0.5 + t * 0.5) = 48 (3.5 + 0.5t) = 48 Solving 3.5 + 0.5t = 48 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + 0.5t = 48 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + 0.5t = 48 + -3.5 0.5t = 48 + -3.5 Combine like terms: 48 + -3.5 = 44.5 0.5t = 44.5 Divide each side by '0.5'. t = 89 Simplifying t = 89
| -26=2u | | -(2x+7)(5x+6)= | | 7x-5=40-x | | (-2x+7)(5x+6)= | | 7x-16=-x+16 | | 4a-9=2(a+1)+13a+1 | | 7(5x+3)(2x+1)= | | 32*17= | | 7(5x-3)(2x-1)= | | 23*17= | | x^2+6x+y^2+6y+14=0 | | 6y=150 | | 11a+14=77-7a | | 45x-16=5-50x | | y-36=48 | | 5(x+2)-(8-x)=0 | | 6y^2-10y+9=0 | | 7x-5=4x+28 | | 9x+5=7x+41 | | .4x=x-500 | | 9cos(2x)=27cos-18 | | 0.5w+9=0.8w-9 | | 36x+2=182 | | 15x-52=8 | | 18+3x=54 | | 2x-4=8-4x | | 8x+27=59 | | 1=37-5x-11 | | 5(2y+3)=75 | | -21+3x=30 | | 27^(1/3) | | 53.5+y=115.5 |